2011
DOI: 10.3111/13696998.2011.635229
|View full text |Cite
|
Sign up to set email alerts
|

Real-life treatment patterns, compliance, persistence, and medication costs in patients with hypertension in Germany

Abstract: The study shows considerable variations in ARB treatment patterns among patients, with the majority of patients treated with fixed-dose or semi-fixed combination therapy. Fixed-dose combinations of ARBs with HCT and/or AML seem to result in better compliance and persistence compared to unfixed regimes of these drug classes, leading to reduction in all-cause hospitalizations, emphasizing the benefit and potential cost-savings of using fixed-dose regimes in a real-life general practice setting in Germany.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…The total cost of CV events attributable to hypertension was estimated to exceed €51.3 [18] 81,843,743 [19] 46,815,916 [20] 65,281,000 [21] 52,642,500 [22] Percentage of females 51.48 % [18] 50.87 % [19] 50.65 % [20] 51.57 % [21] 50.84 % [22] Percentage of females; age C 30 years 71.76 % [18] 70.86 % [19] 69.37 % [20] 64.76 % [21] 63.54 % [22] Percentage of males; age C 30 years 68.59 % [18] 68.33 % [19] 67.05 % [20] 61.39 % [21] 61. 17 Percentage of diagnosed and treated hypertensive subjects 73.00 % [30] 77.00 % [31] 59.40 % [26] 56.92 % [27,29] 58.38 % [32] Percentage of diagnosed patients with adherence C80 % 41.50 % [9] 66.90 % [13] 39.40 % [14] 39.00 % [12] 56.85 % [11] billion over a time span of 10 years (range €5.0 in England and €17.1 in Germany). Considering only the costs associated with diagnosed and treated patients, drug cost is estimated, on average, to represent 37 % (range 10 % in England and 71 % in Spain) of the total cost of the disease and the remaining part being attributed to hospitalisations (Table 5).…”
Section: Scenarios and Sensitivity Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The total cost of CV events attributable to hypertension was estimated to exceed €51.3 [18] 81,843,743 [19] 46,815,916 [20] 65,281,000 [21] 52,642,500 [22] Percentage of females 51.48 % [18] 50.87 % [19] 50.65 % [20] 51.57 % [21] 50.84 % [22] Percentage of females; age C 30 years 71.76 % [18] 70.86 % [19] 69.37 % [20] 64.76 % [21] 63.54 % [22] Percentage of males; age C 30 years 68.59 % [18] 68.33 % [19] 67.05 % [20] 61.39 % [21] 61. 17 Percentage of diagnosed and treated hypertensive subjects 73.00 % [30] 77.00 % [31] 59.40 % [26] 56.92 % [27,29] 58.38 % [32] Percentage of diagnosed patients with adherence C80 % 41.50 % [9] 66.90 % [13] 39.40 % [14] 39.00 % [12] 56.85 % [11] billion over a time span of 10 years (range €5.0 in England and €17.1 in Germany). Considering only the costs associated with diagnosed and treated patients, drug cost is estimated, on average, to represent 37 % (range 10 % in England and 71 % in Spain) of the total cost of the disease and the remaining part being attributed to hospitalisations (Table 5).…”
Section: Scenarios and Sensitivity Analysesmentioning
confidence: 99%
“…A level of good adherence needed for a pharmacological treatment to be effective is widely recognized to be around 80 % of the prescribed therapy [9]. Existing research shows that in several European countries \60 % of treated hypertensive subjects have an adherence to their treatment over 80 % [10][11][12][13][14]. Poor adherence results in severe losses in terms of clinical efficacy and economic efficiency, especially as the cardiovascular events that full adherence could avoid translate into greater hospitalisation costs.…”
Section: Introductionmentioning
confidence: 99%
“…And while FDCs may improve adherence to both medicines, an individual initiating on a free combination has more freedom to switch to other medicines and doses and to discontinue only one of the two medicines if necessary. Further, there is a risk of publication bias, as nearly all studies were conducted or funded by pharmaceutical companies; [15][16][17]23,[43][44][45][46][47][48][49][50][51][52] research has shown that industry-sponsored studies tend to produce favourable results. 53 This study is one of the few studies of adherence to FDCs conducted arm's length to industry.…”
Section: Discussionmentioning
confidence: 99%
“…SPC may also decrease the costs for BP management as shown in Swiss and German primary care. 12 , 13 …”
Section: Discussionmentioning
confidence: 99%
“… 9 11 In clinical trials and cohort studies, SPC of antihypertensive agents are associated with a significant improvement in compliance and with nonsignificant beneficial trends in BP and adverse effects as compared with the same substances given as individual pills. 11 In general practice, SPC seem to be broadly used nowadays, 12 14 and some reports describe a higher likelihood of successful BP control when substances are given as SPC instead of FIC. 15 This suggests that the superior efficacy of SPC documented in controlled clinical trials 16 may translate into improved BP control in daily practice.…”
Section: Introductionmentioning
confidence: 99%